A Comprehensive Review of Genus Sanguisorba: Traditional Uses, Chemical Constituents and Medical Applications - Zhou, Ping; Li, Jingyan; Chen, Qi; Wang, Long; Yang, Jing; Wu, Anguo; Jiang, Nan; Liu, Yuanzhi; Chen, Jianping; Zou, Wenjun; Zeng, Jing; Wu, Jianming (Frontiers in Pharmacology, 2021)
Genus Sanguisorba (family: Rosaceae) comprises nearly 30 species, distributed widely across the temperate and subtropical regions of the Northern Hemisphere. Sanguisorba officinalis L. (S. officinalis) has been used as a hemostatic and scald treating medicine in China for a long time. Numerous studies have demonstrated that plant extracts or monomers from S. officinalis exhibit several pharmacological effects, such as anti-cancer, anti-virus, anti-inflammation, anti-bacteria, neuroprotective and hepatoprotective effects. The other species of genus Sanguisorba are also being studied by researchers worldwide. Sanguisorba minor Scop. (S. minor), as an edible wild plant, is a common ingredient of the Mediterranean diet, and its young shoots and leaves are often mixed with traditional vegetables and consumed as salad. Reports on genus Sanguisorba available in the current literature were collected from Google Scholar, Web of Science, Springer, and PubMed. The Plant List (http://www.theplantlist.org./tpl1.1/search?q=Sanguisorba), International Plant Name Index(https://www.ipni.org/?q=Sanguisorba) and Kew Botanical Garden(http://powo.science.kew.org/ ) were used for obtaining the scientific names and information on the subspecies and cultivars. In recent years, several in vivo and in vitro experiments have been conducted to reveal the active components and effective monomers of S. officinalis and S. minor. A total of 276 compounds have been isolated and identified so far from the species belonging to genus Sanguisorba. Numerous reports on the chemical constituents, pharmacologic effects, and toxicity of genus Sanguisorba are available in the literature. This review provides a comprehensive understanding of the current traditional applications of plants, which are supported by a large number of scientific experiments. Owing to these promising properties, this species is used in the treatment of various diseases, including influenza virus infection, inflammation, Alzheimer's disease, type 2 diabetes and leukopenia caused by bone marrow suppression. Moreover, the rich contents and biological effects of S. officinalis and S. minor facilitate these applications in dietary supplements and cosmetics. Therefore, the purpose of this review is to summarize the recent advances in the traditional uses, chemical constituents, pharmacological effects and clinical applications of genus Sanguisorba. The present comprehensive review may provide new insights for the future research on genus Sanguisorba.